UJIAN SEBAGAI DASAR PEMBENTUKAN DAN PENGUATAN KETAHANAN KESEHATAN MENTAL: KAJIAN SURAH AL-BAQARAH AYAT 155-157 - Bunga Fitri Dayu; Mochammad Novendri Saputra; Syafi'i Syafi'i (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study aims to examine trials in the Qur'an, which can serve as a foundation for the formation and strengthening of mental health from a psychological perspective. The focus of this study is an analysis of Surah Al-Baqarah, verses 155–157, which describes various forms of life's trials, spiritual responses to them, and the rewards obtained. Using a qualitative method through a library approach, this study examines various sources such as the interpretations of Ibn Kathir, Al-Qurthubi, and psychological literature and resilience theory. The results of the study indicate that facing trials in Islam is not merely a passive attitude, but an active process in which the practice of patience and istirja' becomes a spiritual force that maintains the stability of one's emotions, thoughts, and behavior amidst pressure. The trials contained in Surah Al-Baqarah, verses 155–157 have strong relevance in developing resilience, namely the ability of an individual to recover from adversity and survive in the face of life's pressures. This study proves that trials function as a mechanism for developing mental health, where life's pressures are not seen as destructive, but rather as a medium for constructing mental resilience through the internalization of the values ​​of patience and istirja'.